A synopsis of Microperla (Plecoptera: Peltoperlidae), with a new species from Shaanxi Province of China - Chen, Zhi-Teng; Song, Liang-Dong (Zootaxa, 2019)
A new species of the peltoperlid genus Microperla Chu, 1928, Microperla qinlinga Chen, sp. nov. from Shaanxi Province of northwestern China is described and illustrated. The new species is characterized by the widely rounded ventral lobe in males and the extremely large and bilobed subgenital plate in female. In addition, the taxonomic history and current status of the genus Microperla is reviewed.